2022
DOI: 10.1021/acs.jmedchem.2c00004
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-Amino-3-cyanothiophene Derivatives as Potent STAT3 Inhibitors for the Treatment of Osteosarcoma Growth and Metastasis

Abstract: Osteosarcoma is one of the most common malignant bone tumors. However, the treatment and clinical outcomes of osteosarcoma have hardly changed over the past three decades due to the comprehensive heterogeneity and higher rate of mutation of osteosarcoma. Recent studies have shown that STAT3 has the potential to suppress the proliferation and metastasis of osteosarcoma. In this study, a novel class of 2-amino-3-cyanothiophene derivatives were designed and synthesized to inhibit osteosarcoma by targeting STAT3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The changes of CT perfusion parameters are related to the ultrastructural abnormalities of tumor vessels. Among them, the values of BV and BF are related to the decrease in microvessel density and the degree of microvascular lumen in tumor tissue, which provide a theoretical basis for the clinical application of perfusion imaging and evaluate the curative effect [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The changes of CT perfusion parameters are related to the ultrastructural abnormalities of tumor vessels. Among them, the values of BV and BF are related to the decrease in microvessel density and the degree of microvascular lumen in tumor tissue, which provide a theoretical basis for the clinical application of perfusion imaging and evaluate the curative effect [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a range of STAT3 inhibitors under preclinical development and in clinical trials. , For instance, Stattic , STA-21 , BP-1-102 , S31-201 , HJC0152 , HJC0123 , and HJC0416 , as orally bioavailable STAT3 inhibitors, exhibit promising antitumor effects against various cancers in preclinical models in vitro and in vivo. Additionally, a few STAT3 inhibitors, such as TTI-101 and OPB-111077 , have advanced to phase I clinical trials in patients with diverse types of cancers, including GC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to STAT3 inhibitors entering clinic studies, many preclinical STAT3 inhibitors have been reported. For instance, compounds 1d (BP-1-102), 1e (HJC0416), and 1f display potent antitumor activities by inhibiting STAT3 activation (Figure ). Most STAT3 inhibitors so far, however, mainly focus on inhibiting STAT3 phosphorylation at Tyr 705 while ignoring the tumorigenicity of Ser 727 phosphorylation. , It is worth noting that the STAT3 PROTAC molecule SD-36 ( 1g ) remarkably inhibits STAT3 phosphorylation at Tyr 705 and Ser 727 by degrading STAT3 protein, leading to complete and durable tumor regression in vivo , indicating that concurrently inhibiting STAT3 dual phosphorylation might block STAT3 activation to a greater extent than suppression of phosphorylation at either site alone …”
Section: Introductionmentioning
confidence: 99%